Heterogenous cancer-associated fibroblasts related tumor microenvironment marked by CD10/KLF4/TIAM1 were identified in pancreatic adenocarcinoma by integrated transcriptomics - Wan, Yu; Hu, Qiong; Sun, Kai; Shi, Jing; Liu, Limei; Zhang, Xiangsong; Huang, Jianjun; Gong, Chulan; Liu, Jinting; Wang, Haijiu; Yan, Jun (Frontiers in Immunology, 2025)
Pancreatic ductal adenocarcinoma (PDAC) is a highly aggressive malignancy characterized by a dense and heterogeneous tumor microenvironment (TME) composed of various cancer-associated fibroblasts (CAFs). In this study, we explored the composition and proportions of CAF subtypes within the PDAC TME and identified three distinct CAF-related TME subtypes: iCAF-rich, myCAF-rich, and PSC-rich. We observed significant heterogeneity in CAF populations across different patients, which correlated with patient prognosis and the mechanical and fibrotic properties of the TME. Our analysis revealed that these CAF subtypes exhibit distinct gene expression profiles, with the myCAF-rich subtype showing upregulation of hypoxia- and glycolysis-related genes, such as LDHA. Furthermore, gene set and survival analyses demonstrated that specific CAF subtypes harbor unique protective and risk factors, which were non-overlapping between the subtypes. These findings suggest that the heterogeneity of CAF subtypes plays a critical role in PDAC progression and therapeutic response. By utilizing multiplex immunohistochemistry and spatial transcriptomics, we also identified key CAF subpopulations, such as iCAF_17, iCAF_19, and myCAF_12, which were found to interact closely with tumor cells and macrophages. In chemotherapy-treated patients, myCAFs were positioned at the tumor boundary, potentially acting as a barrier to tumor invasion. This study provides novel insights into CAF-related TME subtypes, offering a foundation for future therapeutic strategies targeting CAFs in PDAC.